Compatibility of sodium alginate and konjac glucomannan and their applications in fabricating low-fat mayonnaise-like emulsion gels. (1st February 2020) - Yang, Xi; Gong, Tian; Lu, Yue-hong; Li, Anqi; Sun, Lijun; Guo, Yurong
Highlights: When Alg/KGM mixing ratio is lower than 6:4, they are compatible. The compatibility assessed by dilute solution viscometry is consistent with SEM, AFM and TEM. Alg/KGM gels show significant viscoelasticity, thixotropy. Alg/KGM gels can be applied to produce low-fat mayonnaise substitutes/analogues. Abstract: In this study, the compatibility of alginate (Alg) and konjac glucomannan (KGM) in aqueous solutions was evaluated by dilute solution viscometry (DSV). It was found that when Alg: KGM ratio was lower than 6:4 ( w/w ), Alg and KGM were compatible, which was subsequently confirmed by SEM, AFM and TEM. Moreover, by dispersing emulsified oil droplets into Alg gel matrix, followed by addition of KGM to thicken the system, where the ratio of Alg: KGM was 5:5, a class of emulsion gels with significant thixotropy and viscoelasticity could be obtained. The prepared emulsion gels displayed good thermal stability and freeze-thaw stability, with no oil droplet coalescence observed after heating at 100°C for 30 min or freezing the gels at -18°C for 24 h. Overall, the mixed Alg/KGM system is expected to provide a template for designing low-fat mayonnaise-like food emulsions.